2005
DOI: 10.1007/s00268-005-0129-3
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Palliative Gastrectomy in Patients with Stage IV Gastric Cancer?

Abstract: Patients with metastatic gastric cancer are currently not considered operative candidates and are most often offered systemic therapy. Palliative resection of the primary tumor has been considered irrelevant to the outcome and has been recommended only for palliation of symptoms. We have examined the role of palliative gastrectomy and its impact on survival in patients with stage IV gastric cancer at initial diagnosis between 1990 and 2000. A total of 105 patients with stage IV disease were identified during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 23 publications
3
79
0
6
Order By: Relevance
“…A recent meta-analysis of randomized trials that compared chemotherapy and best supportive care in patients with MGC revealed that chemotherapy was more beneficial than best supportive care alone with respect to OS and quality of life [20]. However, the role of surgery (debulking gastrectomy or gastrectomy plus metastasectomy) in GC patients with distant metastasis is still controversial [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The results of our study suggest that surgery may be beneficial in MGC patients when combined with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent meta-analysis of randomized trials that compared chemotherapy and best supportive care in patients with MGC revealed that chemotherapy was more beneficial than best supportive care alone with respect to OS and quality of life [20]. However, the role of surgery (debulking gastrectomy or gastrectomy plus metastasectomy) in GC patients with distant metastasis is still controversial [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The results of our study suggest that surgery may be beneficial in MGC patients when combined with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some retrospective studies have shown significant survival benefits for palliative debulking gastrectomy in patients with MGC [11,[13][14][15][16][17][18]. Based on these results, some experts insist that debulking gastrectomy is the preferred choice for patients with MGC before the initiation of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Palliative resection relieves symptoms as well as maintains survival benefit in advanced gastric cancer. There are several studies that indicate the importance of palliative gastrectomy in Stage IV gastric cancer [1][2][3][4][5][6]. Stage IV gastric cancer is defined according to the American Joint Committeee on Cancer (AJCC, 6th edition), as M 1 , all N 3 , or T 4 N 1-3 M 0 (AJCC, 2003) [7].…”
Section: Introductionmentioning
confidence: 99%